Kinetics of hydrogen generation from hydrolysis of sodium borohydride on Pt/C catalyst in a flow reactor. (25th February 2013) - Boran, Asli; Erkan, Serdar; Ozkar, Saim; Eroglu, Inci
SUMMARY Here, we report the results of a kinetic study on the hydrogen generation from the catalytic hydrolysis of sodium borohydride in a differential flow reactor. As catalyst platinum supported on carbon (Pt/C) was used in two forms: either as powder or coated on carbon cloth. For optimization of the system several parameters such as sodium hydroxide concentration, sodium borohydride concentration and the flow rate of the feed solution were varied. It was found that the H2 generation rate increases with an increase in NaBH4 concentration whereas it shows a slight decrease with variation in NaOH concentration. As an important parameter, an increase in the flow rate of feed solution enhances the hydrogen generation rate. This is an important result as it provides an easy control of reaction or hydrogen generation on demand. Copyright © 2013 John Wiley & Sons, Ltd.